Entertainment Tax in Indonesia and Its Comparison with Malaysia as an Opportunity for Policy Reforms: A Systematic Literature Review - Tasya Yora Yolanda; Umanto, Umanto (Institut Bisnis dan Informatika Kesatuan, 2025)
Entertainment tax is an important source of Local Revenue (PAD) in Indonesia, but its effectiveness as a regulatory and fiscal tool still faces various challenges, especially related to regional variations in collection and compliance levels. This study is a systematic literature review of articles published between 2020 and 2024, using a qualitative approach to analyze tax collection efficiency, classification changes, and the impact of the COVID-19 pandemic on entertainment tax revenues. The findings show that although entertainment tax contributes significantly to PAD, high rates often depress the profitability of the entertainment sector such as nightlife and recreation venues, thus affecting consumer behavior and encouraging tax evasion. Local governments also face limitations in supervision and law enforcement. A comparative study with Malaysia reveals that the implementation of transparency, consistent supervision, and strict sanctions can improve compliance and regulatory effectiveness. Therefore, policy reforms are needed that are able to balance fiscal objectives with the sustainability of the entertainment sector, through improving governance and adjusting tariff policies so as not to cause excessive burdens for business actors.